PENGARUH LOKASI, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ULANG DI TOKO ERA DUNIA - I Wayan Egi Permana; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
The purpose of this study was to find out how the decision to repurchase at Toko Era Dunia. The independent variables used are location, promotion and service quality. This study uses a questionnaire method in obtaining related data and information for analysis. The data used in this study is primary data obtained from the results of filling out questionnaires by respondents who have purchased products at the World Era Store. Sampling in this study used the hair technique by counting the number of questionnaire items multiplied by the number of margins of error. The number of samples in this study was 100 data. The data analysis method used is the classical assumption test and multiple linear regression. This study uses the t test to determine the significance of the effect of the independent variable on the dependent variable partially. The results of this study indicate that the independent variable has a positive and significant effect on repurchase decisions at Toko Era Dunia.